INTEGRATED APPROACH TO ANTICOAGULANT TREATMENT IN PATIENTS WITH ATRIAL FIBRILLATION: A COMPARATIVE ANALYSIS OF EFFICACY, SAFETY, AND MORTALITY RISK - Szymon Antoni Kaźmierczak,; Aleksandra Maria Śledziewska,; Julia Delfina Latocha,; Aleksandra Kołdyj, (International Journal of Innovative Technologies in Social Science, 2025)
Atrial fibrillation (AF) remains the most common sustained cardiac arrhythmia, profoundly increasing the risk of thromboembolic events, particularly debilitating ischemic stroke. Oral anticoagulation (OAC) is the cornerstone of stroke prevention in AF. The therapeutic landscape has been revolutionized by the advent of direct oral anticoagulants (DOACs), challenging the long-standing dominance of vitamin K antagonists (VKAs). This review critically examines the integrated approach to anticoagulant treatment in AF, delving into comparative efficacy, safety profiles, and the crucial aspect of mortality risk associated with different OAC regimens. We inquire into which therapeutic strategies offer the most favorable outcomes, considering the nuanced evidence from recent PubMed literature. Emphasis is placed on personalized medicine, comprehensive risk stratification, the indispensable role of multidisciplinary care, adherence optimization, and tailored management for diverse patient populations.